IMPLEMENTASI PROGRAM KELUARGA HARAPAN DALAM PEMBERDAYAAN KELUARGA PENERIMA MANFAAT DI KECAMATAN BUNGKU TENGAH KABUPATEN MOROWALI - Masyhar, Masyhar; Tindjabate, Christian; Alamsyah, M. Nur (Katalogis, 2021)
The research aims to analyze the Implementation of the Program Keluarga Harapan  for empowering beneficiary families   in Central Bungku sub-district, Morowali district. The research method used is descriptive qualitative method and data collection techniques by means of observation, interviews, and documentation. The main theory as the reference in this research was adopted from George C. Edward III with four dimension, namely communication, resources, disposition, and bureaucratic  structure. The selection of informants with a purposive technique. by following procedures namely data reduction, data presentation and conclusion (verification). The results showed that the Implementation of the Program keluarga Harapan for empowering beneficiary families in Bungku Tengah Subdistrict, Morowali District was not optimal, where from the Communication aspect, the PKH Implementer in Bungku Tengah Subdistrict, Morowali District had established communication between the parties, however socialization was not routinely carried out to StakeHolders, especially cross officials agencies that need that information. Where officials often change personnel because of the transfer of positions at a certain time, or when the distribution of information is carried out is unable to attend. From the aspect of resources (Resouces), PKH Human Resources (SDM) are sufficient in terms of quantity and capability and knowledge but have not yet been supported by the amount of sharing funds that should be provided by the Regional Government at least 5 (five) percent according to the Social Minister's circulation of PKH facilities and infrastructure. in Morowali district. As for the aspect of the Implementing Attitude, from the Loyalty side, the Commitment and honesty of the implementer in implementing the Family Hope Program has been carried out in accordance with the code of ethics established by the institution, and from the aspect of the Bureaucratic Structure. , also the distribution of authority and hierarchy has been running quite synergistically between the unit of government units involved.